MANAJEMEN SDM DALAM PRESPEKTIF EKONOMI ISLAM : TINJAUAN MANAJEMEN SDM DALAM INDUSTRI BISNIS - Teguh Suripto (JESI (Jurnal Ekonomi Syariah Indonesia), 2012)
Abstract Management is one branch of economics that plays an important role in the successful management of an organization or company. Implementation of the company's management can improve the effectiveness and efficiency of resource companies or organizations so as to achieve the goal or vision of a better company. Islam is one religion the religion professed by the majority of the Indonesian population, have given color to every aspect of life of its adherents. Started in terms of religious, political, social and economic. Conventional economic outlook puts worldliness course, has not looked at his spiritual needs. So that employees only be the object of the company and not be subject to the company. With the implementation of the Human Resources Management Islam, the employee will be subject to the company so that they are able to participate actively for the betterment of the company. Islamic economic system in implementing human resource management, based on the harmony or balance between the need to do material and human ethics. Islamic Economic System not forget the main features of human progress, which is dependent on the extent to which the smooth coordination and harmony between the moral and material aspects of human life. Key word : Management SDM, Islamic Economic, Recruitment, Selection, training and development